A genome-wide association meta-analysis implicates Hedgehog and Notch signaling in Dupuytren’s disease - Riesmeijer, Sophie A.; Kamali, Zoha; Ng, Michael; Drichel, Dmitriy; Piersma, Bram; Becker, Kerstin; Layton, Thomas B.; Nanchahal, Jagdeep; Nothnagel, Michael; Vaez, Ahmad; Hennies, Hans Christian; Werker, Paul M. N.; et al. (Nature communications, 2024)
Dupuytren’s disease (DD) is a highly heritable fibrotic disorder of the hand with incompletely understood etiology. A number of genetic loci, including Wnt signaling members, have been previously identified. Our overall aim was to identify novel genetic loci, to prioritize genes within the loci for functional studies, and to assess genetic correlation with associated disorders. We performed a meta-analysis of six DD genome-wide association studies from three European countries and extensive bioinformatic follow-up analyses. Leveraging 11,320 cases and 47,023 controls, we identified 85 genome-wide significant single nucleotide polymorphisms in 56 loci, of which 11 were novel, explaining 13.3–38.1% of disease variance. Gene prioritization implicated the Hedgehog and Notch signaling pathways. We also identified a significant genetic correlation with frozen shoulder. The pathways identified highlight the potential for new therapeutic targets and provide a basis for additional mechanistic studies for a common disorder that can severely impact hand function. In this meta-analysis of the fibrotic hand disorder Dupuytren’s disease, the authors identify genetic risk variants, study them for their functional consequences and implicate two signaling pathways involved in the disease mechanism of this debilitating disorder.